Towards Enhanced MRI Performance of Tumor-Specific Dimeric Phenylboronic Contrast Agents - Jonathan Martinelli; Lorenzo Tei; Simonetta Geninatti Crich; Diego Alberti; Kristina Djanashvili (Molecules, 2021)
It is known that phenylboronic acid (PBA) can target tumor tissues by binding to sialic acid, a substrate overexpressed by cancer cells. This capability has previously been explored in the design of targeting diagnostic probes such as Gd- and 68Ga-DOTA-EN-PBA, two contrast agents for magnetic resonance imaging (MRI) and positron emission tomography (PET), respectively, whose potential has already been demonstrated through in vivo experiments. In addition to its high resolution, the intrinsic low sensitivity of MRI stimulates the search for more effective contrast agents, which, in the case of small-molecular probes, basically narrows down to either increased tumbling time of the entire molecule or elevated local concentration of the paramagnetic ions, both strategies resulting in enhanced relaxivity, and consequently, a higher MRI contrast. The latter strategy can be achieved by the design of multimeric GdIII complexes. Based on the monomeric PBA-containing probes described recently, herein, we report the synthesis and characterization of the dimeric analogues (GdIII-DOTA-EN)2-PBA and (GdIII-DOTA-EN)2F2PBA. The presence of two Gd ions in one molecule clearly contributes to the improved biological performance, as demonstrated by the relaxometric study and cell-binding investigations.